219k views
4 votes
Help!!!!!¡!!¡!!!!!!!

Help!!!!!¡!!¡!!!!!!!-example-1

2 Answers

5 votes

\sqrt{a}(2a^2 - \dfrac{4}{a}) =

= a^{\frac{1}{2}}(2a^2 - 4a^{-1})

= 2a^2a^{\frac{1}{2}} - 4a^{-1}a^{\frac{1}{2}}

= 2a^{\frac{4}{2}}a^{\frac{1}{2}} - 4a^{-\frac{2}{2}}a^{\frac{1}{2}}

= 2a^{\frac{5}{2}} - 4a^{-\frac{1}{2}}


User Przemek
by
6.9k points
1 vote

√(a)(2a^2 - (4)/(a)) =


= a^{(1)/(2)}(2a^2 - 4a^(-1))


= 2a^2a^{(1)/(2)} - 4a^(-1)a^{(1)/(2)}


= 2a^{(4)/(2)}a^{(1)/(2)} - 4a^{-(2)/(2)}a^{(1)/(2)}


= 2a^{(5)/(2)} - 4a^{-(1)/(2)}







User Khaled Garbaya
by
5.8k points